Frenet equations of spacelike biharmonic curves with timelike binormal in terms of exponential maps according to flat metric in lorentzian heisenberg group heis3 - Körpinar, Talat; Turhan, Essin (My University, 2013)
In this paper, we study Frenet representations of spacelike biharmonic curves with timelike binormal according to flat metric in the Lorentzian Heisenberg group Heis 3. We characterize spacelike biharmonic curves with timelike binormal in terms of exponential maps in the Lorentzian Heisenberg group Heis 3. © IDOSI Publications, 2013.
Keywords: Biharmonic curve; Flat metric; Heisenberg group